Core technologies for hydropower digitalization within the Energy Internet framework: a mini-review - Cao, Tingxiang; Gao, Song; Shi, Xiangjian; Mo, Li; Zhang, Bing; Zhu, Jingan (Frontiers in Water, 2025)
Hydropower, a cornerstone renewable energy source globally, is undergoing a transformative evolution through digitalization technologies within the emerging Energy Internet paradigm. This review examines the critical role, applications, enabling architectures, security considerations, and future directions of hydropower digitalization. Digitalization optimizes resource allocation and accessibility, enabling enhanced operational oversight and integration. Key applications include smart monitoring via Internet of Things (IoT) sensors and big data analytics for predictive maintenance, digital twin implementation for equipment prognostics and optimized real-time dispatch, sophisticated water resource scheduling leveraging diverse datasets (meteorological, hydrological, grid demand) for maximized utilization efficiency, and ecological impact mitigation via intelligent flow control and habitat design simulation. Deployment necessitates robust security measures adhering to industrial control standards (e.g., IEC 62443) and often employs redundant network architectures (dual-active or independent operation) to ensure safety and continuity. Future advancement depends critically on progress in interoperability, next-generation predictive digital twins, edge computing, advanced communication infrastructure, and cybersecurity resilience. Collectively, the ongoing evolution of hydropower digitalization technologies represents a vital pathway toward realizing the goals of efficiency, stability, and sustainability within the global Energy Internet.